STUDENTS' QUESTIONSON INQUIRY-TYPE LABORATORY IN LEARNING HEAT TRANSFER CONCEPT - Novianti, Anggita (2015)
This study investigated the current profile of students' question during an inquiry-type laboratory activity. 7th grade students were studying heat transfer through an inquiry-type laboratory activity. A short passage was given to students to initiate a problem in a form of investigative question and the students were asked to design an experiment in order to answer their own questions. Four groups of students from two different class were video and audio-taped. The questions were collected through worksheet and the recordings of the students' discourse during the activity. The result shows that the students' asked 41 different productive questions and 34 non-productive questions at the planning stage. It can be seen that the students asked more productive question when they were asked to write down the question on the worksheet compared to when they were having group work activity. At the experiment stage, 8 productive questions and 19 non-productive questions were obtained. The number decreased as the students were setting up the experiment, observing and analyzing. During the discussion stage, the number had significantly decreased into only 6 productive questions and 2 non-productive questions. Productive question was mostly arisen at the planning stage where the students were trying to identify the problem and constructing an investigative question for them to solve. Further research should be able to describe how asking better questions helps students to learn more. ••• Keywords Students' question, Inquiry-type laboratory, Heat transfer, productive question, non-productive question Penelitian ini mencari profil terkini dari pertanyaan siswa dalam sebuah kegiatan laboratorium inkuiri. Siswa kelas 7 sedang mempelajari materi perpindahan panas melalui kegiatan laboratorium inkuiri. Sebuah wacana pendek diberikan kepada siswa untuk merangsang timbulnya permasalahan dalam bentuk pertanyaan investigasi, kemudian siswa diminta untuk membuat sebuah eksperimen untuk menjawab pertanyaan mereka sendiri. Empat kelompok siswa dari dua kelas yang berbeda direkam secara video dan audio. Pertanyaan dikumpulkan melalui lembar kerja siswa dan hasil rekaman suara percakapan siswa selama kegiatan berlangsung. Hasilnya menunjukkan bahwa siswa mengajukan 41 pertanyaan produktif yang berbeda dan 34 pertanyaan tidak produktif pada tahap perencanaan. Dapat terlihat bahwa siswa mengajukan pertanyaan produktif lebih banyak ketika diminta untuk menuliskan pertanyaan pada lembar kerja daripada ketika siswa mengajukan pertanyaan secara verbal pada saat kegiatan berlangsung. Pada tahap eksperimen, 8 pertanyaan produktif dan 19 pertanyaan tidak produktif didapatkan. Jumlah pertanyaan siswapun berkurang ketika siswa menyiapkan eksperimen, mengobservasi, dan menganalisa. Pada tahapan diskusi, jumlah pertanyaan siswa menurun drastis menjadi hanya 6 pertanyaan produktif dan 2 pertanyaan tidak produktif. Pertanyaan produktif sering diajukan oleh siswa pada tahap perencanaan dimana siswa berusaha mengidentifikasi masalah dan menyusun pertanyaan investigasi untuk siswa selesaikan. Penelitian selanjutnya dapat menjelaskan bagaimana mengajukan pertanyaan yang lebih baik dapat membantu siswa untuk belajar lebih banyak. ••• Kata Kunci Pertanyaan siswa, Laboratorium inkuiri, Perpindahankalor, Pertanyaanproduktif, Pertanyaantidakproduktif